Activated protein C accelerates venous thrombus resolution through heme oxygenase‐1 induction. (January 2014) - Gabre, J.; Chabasse, C.; Cao, C.; Mukhopadhyay, S.; Siefert, S.; Bi, Y.; Netzel‐Arnett, S.; Sarkar, R.; Zhang, L.
Summary Background Thrombus resolution is a complex process that involves thrombosis, leukocyte‐mediated thrombolysis, and the final resolution of inflammation. Activated protein C (APC) is an anticoagulant that also possesses immunoregulatory activities. Aim In this study, we sought to examine the effects of APC administration on thrombus resolution using a mouse model of deep vein thrombosis by ligating the inferior vena cava (IVC). Methods The IVCs of C57BL/6 mice were ligated. Beginning on day 4 post IVC ligation, mice were injected intraperitoneally daily with APC, APC plus an heme oxygenase‐1 (HO‐1) inhibitor Sn‐protoporphyrin IX (SnPP), SnPP alone, or vehicle control. At different time points following surgery, the thrombus‐containing IVCs were weighed and then analyzed by use of biochemical assays and histology. Results Venous thrombi reached maximum size on day 4 post ligation. The APC‐treated group exhibited a significant reduction in thrombus weights on day 12 but not on day 7 compared with control mice. The enhanced thrombus resolution in APC‐treated mice correlated with an increased HO‐1 expression and a reduced interleukin‐6 production. No significant difference was found in urokinase‐type plasminogen activator, plasminogen activator inhibitor‐1, or matrix metalloproteinase‐2 and ‐9 between APC‐treated and control mice. Coinjection of the HO‐1 inhibitor SnPP abolished the ability of APC to enhance thrombus resolution. Conclusions Our data show that APC enhances the resolution of existing venous thrombi via a mechanism that is in part dependent on HO‐1, suggesting that APC could be used as a potential treatment for patients with deep vein thrombosis to accelerate thrombus resolution.